Data accuracy in capture fisheries production at Cilacap Ocean Fishing Port - Ernani Lubis; Anwar Bey Pane; Putri Nirwana Paramita (Depik, 2021)
Accurate capture fishery production data at the fishing ports is crucial, especially for planning the development of capture fisheries and fishing ports. This research aims to analyze the mechanism and accuracy in collecting capture fishery data at the fishing port, especially Cilacap Ocean Fishing Port (OFP). The data collection mechanism of capture fishery production is analyzed through a qualitative descriptive method, while the accuracy of the data was analyzed with a comparative quantitative descriptive method. The results showed three steps in the data collection mechanism at Cilacap OFP: data collection, data recapitulation, and data reporting. The values of deviation and accuracy level of the data on capture fishery were 3,4%-62,1% and 37,9%-96,6%, respectively. This result concluded that the data recorded by the enumerator were more accurate than those in the logbook classified as inaccurate.Keywords:CilacapDataFishAccurateFishing Port